Upcycling Plastic Wastes into Value‐Added Products by Heterogeneous Catalysis. Issue 14 (13th May 2022) - Tan, Tian; Wang, Wei; Zhang, Kai; Zhan, Zixiang; Deng, Weiping; Zhang, Qinghong; Wang, Ye
Abstract: Plastics are playing essential roles in the modern society. The majority of them enter environment through landfilling or discarding after turning into wastes, causing severe carbon loss and imposing high risk to ecosystem and human health. Currently, physical recycling serves as the primary method to reuse plastic waste, but this method is limited to thermoplastic recycling. The quality of recycled plastics gradually deteriorates because of the undesirable degradation in the recycling process. Under such background, catalytic upcycling, which can upgrade various plastic wastes into value‐added products under mild conditions, has attracted recent attention as a promising strategy to treat plastic wastes. This Review highlights recent advances in the development of efficient heterogeneous catalysts and useful strategies for upcycling plastics into liquid hydrocarbons, arene compounds, carbon materials, hydrogen, and other value‐added chemicals. The functions of catalysts and the reaction mechanisms are discussed. The key factors that influence the catalytic performance are also analyzed. Abstract : One man's trash : Chemical upcycling represents a promising strategy to deal with the challenge caused by plastic wastes. Here, recent advances in the catalytic upcycling of various plastic wastes into value‐added chemicals and fuels are highlighted, with emphasis on heterogeneous catalysis. Typical heterogeneous catalysts, reaction mechanism, and other key factors that influence the upcycling efficiency are discussed.